Efektivitas Program Pendidikan dan Pelatihan (Diklat) dalam Meningkatkan Kinerja Pegawai Negeri Sipil di Kota Padang - Husna, Nilam Akhsanul; Aqilah, Nabila Siti; Novita, Nada Febri; Hanoselina, Yulia (PT Maju Malaqbi Makkarana, 2024)
Education and Training (Diklat) is a program organized by the government to develop employee skills in the fields they work in. This is explained in Government Regulation Number 101 of 2000 concerning Civil Servant Job Education and Training, which states that Diklat is a learning process that aims to improve the abilities of Civil Servants. Therefore, the Diklat program in government agencies must receive serious attention, considering the importance of this initiative in improving employee performance. This study aims to analyze the effectiveness of the Diklat program in improving employee performance in Padang City. The method used in this study is qualitative, especially literature studies, which allows for the collection of relevant information and data analysis. The results of the study indicate that the implementation of the education and training program faces several obstacles, especially related to facilities and infrastructure. The main problem faced is the limited costs or budget needed to organize the Diklat program effectively. This limitation can hinder the quality and scope of training, thus impacting the achievement of the goal of improving employee performance. Therefore, more attention is needed to the funding aspect to ensure the success of the Diklat program in the future.